Ureterovaginal Fistula and Laparoscopic Repair: A Case Report and Literature Review - Vázquez-Chalé Brian Isaí de Jesús; Millán-Flores Ricardo Alexander; Gómez-Lara Miguel Humberto; Narváez-Morales José Antonio (International Journal of Medical Science and Clinical Research Studies, 2026)
Iatrogenic ureteral injuries are mainly associated with gynecologic procedures and other abdominopelvic interventions. They may go unrecognized during surgery and subsequently present with pain, fever, urinoma, obstruction, deterioration of renal function on serum biochemical testing, or vaginal urinary leakage after a fistulous tract forms between the ureter and vagina. In ureterovaginal fistulas, ureteral stenting is an initial option in selected patients; when it fails or when a complex distal injury is present, ureteral reimplantation is the definitive treatment, either through an open or laparoscopic approach. A psoas hitch brings the bladder closer to the viable ureter and facilitates a tension-free anastomosis. We present a case of a delayed right ureterovaginal fistula after myomectomy, treated with laparoscopic Lich-Gregoir ureteral reimplantation plus psoas hitch, resulting in resolution of the leakage and recovery of biochemical renal function.